TOURISM COMMUNICATION SOCIOLOGY: A NARRATIVE REVIEW OF THEORETICAL AND CONCEPTUAL DEVELOPMENTS IN THE DIGITAL ERA - Zulkifli Hi.Saleh (International Journal of Multidisciplinary Reseach, 2026)
The advancement of digital technology has fundamentally transformed the tourism industry, shifting it from a linear promotional model to an interactive, participatory, and platform-based communication ecosystem. This article aims to narratively examine the development of theories and concepts in the sociology of tourism communication, with particular emphasis on the dynamics of meaning construction, social interaction, and power relations within digital contexts. This study employs a narrative literature review approach by analyzing recent scholarly works indexed in the Scopus database within the 2019–2024 period. The findings reveal that the sociology of tourism communication has evolved across five major clusters: the construction of meaning and destination representation, symbolic interaction in tourism experiences, digitalization and communication platforms, power relations and hegemony, as well as intercultural communication and identity. Furthermore, the study identifies a paradigm shift from functionalist approaches toward constructivist and critical perspectives, in line with the increasing role of digital technology in shaping the social reality of tourism. Nevertheless, gaps remain in the integration of classical communication sociology theories with contemporary digital phenomena, as well as in the limited attention given to Global South contexts. This article contributes by providing a comprehensive theoretical synthesis while proposing future research agendas in the field of tourism communication sociology.